Gut Microbiota’s role in lipoma development: evidence from mendelian randomization - Li, Yuxin; Chen, Jiahao; Yao, Hang; Xu, Xiaogang; Zheng, Xianglong; Wang, Yu; Wang, Wanchun (Frontiers in Genetics, 2024)
BackgroundLipoma, a benign tumor derived from mesenchymal tissue, significantly affects patients’ physical and psychological wellbeing. Increasing evidence points to a strong link between the gut microbiome (GM) and lipoma incidence. This study utilizes Mendelian Randomization (MR) to assess the potential causal relationships between the GM and lipoma development.MethodsWe conducted a two-sample MR analysis using genome-wide association study (GWAS) data from MiBioGen and FinnGen to explore the causal relationship between GM and lipoma. The GM dataset included 18,340 participants with 14,587 single nucleotide polymorphisms (SNPs), while the lipoma dataset comprised 412,181 participants with 21,306,349 SNPs. We employed 5 MR methods: Inverse Variance Weighted (IVW), Weighted Median, Simple Mode, MR-Egger, and Weighted Mode. Additional assessments included Cochran’s Q test for result heterogeneity, PRESSO analysis for horizontal pleiotropy, and sensitivity analyses through scatter plots, leave-one-out analyses, funnel plots, and forest plots.ResultsThe IVW method identified 18 gene predictors trans-genus associated with lipoma risk. Protective effects against benign lipoma (BL) were observed in the Eubacterium rectale group, Desulfovibrio, Ruminococcus1, Clostridium sensu stricto1, and Lachnospiraceae UCG001; conversely, Lachnospiraceae UCG008 was linked to increased BL risk. Desulfovibrio provided protection against TS-BL; however, the Family XIII AD3011 group, Eubacterium coprostanoligenes group, Lachnospiraceae NK4A136 group, and Parasutterella were associated with an increased TS-BL risk. The Clostridium innocuum group, Eubacterium rectale group, Anaerotruncus, Ruminiclostridium6, and Lachnospiraceae UCG001 offered protection against LS-BL, while Lachnospiraceae UCG008 was linked to an increased LS-BL risk. The Eubacterium brachy group, Odoribacter, Butyricimonas, Subdoligranulum, and Clostridium sensu stricto1 were protective against HFNS-BL; Ruminococcaceae UCG005 was associated with an increased HFNS-BL risk.ConclusionCompared to malignant tumors, research on lipomas has been relatively limited. This study, through MR analysis, provided new evidence of a causal relationship between specific GM and the development of lipomas. Certain gut bacterial species may act as protective or harmful factors in lipoma formation, offering new avenues for future treatment strategies. However, additional research is required to unravel the complexity of how GM influences the pathogenesis of lipomas.